Hubungan Fear of Missing Out (FoMO) dengan Kesejahteraaan Psikologi pada Mahasiswa yang Sedang Mengerjakan Skripsi - Shafira Daffanur; Debora Basaria; Astri Anggraini (Dinasti Research, 2025)
Completing a thesis is one of the challenges that students face during collage years. In this context, easy access to social media can be a distraction that contributes to internet addiction and FoMO. FoMO, although often perceived as a negative phenomenon, can also motivate social interactions that ultimately support pscyhological well-being.This study aims to explore the relationship between FoMO and psychological well-being in university students who are working on thesis. By using quantitative methods through non-probability sampling technique, this study involved 330 participants who were classified as active students who are working thesis. The measuring instruments chosen in this study are the Fear of Misisng Out Scale (FOMOS) and Ryff Scales of Psychological Well-Being. The results of the analysis with Spearman correlation showed a significant positive relationship between FoMO and psychological well-being (r=0.473, p=0.000) meaning, higher the perceived FoMO, the higher the level of psychological well being. This may be explained by the possibility that the drive to stay socially connected through social media may provide emotional support and a sense of engagement that is important during the thesis process. The findings open up opportunities for further research in identifying factors that may mediate or strengthen this relationship, as well as providing a basis for interventions that can be support students psychological well-being during the thesis period.